Fabrication of n-In6Se7:Sn/p-CuInSe2 heterojunction diode on FTO coated glass substrates using reactive evaporation technique. (February 2020) - Anuroop, R.; Pradeep, B.
Abstract: The heterojunction diode using Sn doped In6 Se7 and CuInSe2 thin films are fabricated on FTO coated glass substrates using reactive evaporation technique. The structure of CuInSe2 film is studied using XRD analysis and the film exhibits polycrystalline nature. XPS result confirms that the prepared sample is nearly stoichiometric. The I–V measurements of FTO/n-In6 Se7 :Sn/p-CuInSe2 /Ag heterojunction diode, in dark condition, shows rectification behavior. The knee voltage and ideality factor of the diode are observed to be 1.52 V, 3.09 V and 5.57, 16.16 respectively when the Sn dopant concentration varied from 0.47 at% to 1.57 at%. The absence of photoresponse from the diodes under illumination condition is explained using the energy band structure of the heterojunction. Highlights: Polycrystalline CuInSe2 thin films are deposited on glass substrates by reactive evaporation technique. CuInSe2 thin film shows a direct band gap value of 1.05 eV. n-In6 Se7 :Sn/p-CuInSe2 heterojunction diodes are prepared on FTO coated glass substrates using reactive evaporation technique. Sn dopant concentration in In6 Se7 intensely affected the ideality factor and series resistance of the prepared diode. An investigation of the band alignment suggests that the prepared heterojunction can be used in photovoltaic applications.